STUDENTS’ ACADEMIC PERFORMANCE ASSESSMENT SYSTEMS AS A TOOL TO CONTROL THE LEVEL OF MASTERY OF EDUCATIONAL PROGRAMS - Vasily S. Senashenko; Gennady F. Tkach (Высшее образование в России)
Assessment systems of students’ academic achievement and their educational outcomesare the object of the study. The comparison of the different assessment systems is performed on the basis of the analysis of their efficiency as a tool of control and assessment of educational outcomes, which carries out a normative, informative and diagnostic function, as well as a control and incentive function during the educational process in higher education.